On the valuation implications of unbundled disclosure - Jia, Xue; Suijs, Jeroen (Contemporary Accounting Research, 2026)
Abstract Firms with multiple pieces of information can disclose the information concurrently (bundled disclosure) or sequentially (unbundled disclosure). This paper examines the pricing implications of (un)bundled disclosure in a rational expectations equilibrium model. The model considers a firm whose liquidating cash flow consists of two components. Some investors possess private information about one component (e.g., earnings) and all investors are uninformed about the other component (e.g., unexpected events). We analyze three disclosure policies. In bundled disclosure, both cash flow components are disclosed concurrently; in unbundled disclosure, the informed cash flow component is disclosed early, and the uninformed component is disclosed later; and in alternative unbundled disclosure, the uninformed component is disclosed early, and the informed component later. We find that the disclosure policy influences the cost of capital prior to any disclosure through a risk allocation effect and a price informativeness effect. Unbundled disclosure results in a lower cost of capital compared to bundled disclosure, as it improves risk allocation and enhances the informativeness of the stock price prior to any disclosure. However, for alternative unbundled disclosure, the cost of capital can be higher or lower than that of the other disclosure policies. This is because late disclosure of the informed cash flow component alters investors' risk exposure to the noisy supply of shares, thereby influencing the risk allocation and price informativeness effects.